Is there a correlation between aberrant embryonic crown-rump length growth velocities and subsequent birth weights?. (17th August 2016) - Mongelli, Max; Lu, Chuan; Reid, Shannon; Stamatopoulos, Nicole; Sankaralingam, Kaantharuban; Casikar, Ishwari; Hardy, Nigel; Condous, George
Abstract : In this study, we tested the hypothesis that anomalous first trimester growth affects birth weight. Four hundred and fifteen women with viable singleton pregnancies at the primary transvaginal scan who had at least two crown rump length (CRL) and birth weight data were included. A linear mixed model was fitted to the Box-Cox transformed CRL values to evaluate the association between the GA and the embryonic growth. For multivariate analysis we included maternal age, height, weight, parity, number of miscarriages, vaginal bleeding, smoking, foetal gender, birth weight, small-for-gestation (SGA) and large-for gestation (LGA) categories at delivery. Smoking appeared to be significant for predicting the initial CRL from the beginning of the pregnancy ( p value = 0.013). The SGA foetuses appeared to have slightly slower embryonic growth rates compared to non-SGA ( p value = 0.045), after taking into account the effect of smoking on the initial CRL. None of the other variables including subsequent birth weight or LGA category have statistically significant effect on the first trimester embryonic growth curve when tested separately.